Inhibition of antimicrobial peptides by group A streptococci: SIC and DRS. (20th March 2006) - Fernie-King, B.A.; Seilly, D.J.; Lachmann, P.J.
Abstract : SIC (streptococcal inhibitor of complement) is a 31 kDa protein secreted by a few highly virulent strains of GAS (group A streptococci), predominantly by the M1 strain. Initially described as an inhibitor of the membrane attack complex of complement, it has turned out to be a polyfunctional inhibitor of the innate mucosal immune response. The SIC protein sequence contains three domains: an N-terminal SRR (short repeat region), followed by three longer tandem repeats [LRR (long repeat region)] and a C-terminal PRR (proline-rich region). SIC inhibits the antibacterial activity of a wide range of antimicrobial peptides and proteins: i.e. lysozyme, SLPI (secretory leucocyte proteinase inhibitor), LL-37, hNP-1 (human neutrophil peptide-1) and the human β-defensins 1, 2 and 3. Analysis of the functional properties of recombinant domains of SIC shows that binding and inhibition of lysozyme and human β-defensin-3 require the SRR+LRR, as does binding to SLPI. Complement inhibition is confined to the SRR. M12 GAS secrete a protein 'distantly related to SIC' (DRS). DRS contains a C-terminal PRR which is significantly similar to that of SIC, but it has no central LRR and the N-terminal SRR is very different. DRS inhibits human β-defensin-3, but has no effect on lysozyme, SLPI or complement.